Rehabilitation, reablement, and restorative care approaches in the aged care sector: a scoping review of systematic reviews - Claire Gough; Raechel A. Damarell; Janine Dizon; Paul D.S. Ross; Jennifer Tieman (BMC Geriatrics)
Abstract Background Ageing populations are set to drive up demand for aged care services, placing strain on economies funding social care systems. Rehabilitation, reablement, and restorative care approaches are essential to this demographic shift as they aim to support independent function and quality of life of older people. Understanding the impact of these approaches requires nuanced insights into their definitions, funding, and delivery within the aged care context. This scoping review mapped and compared systematic review-level research on rehabilitation, reablement, and restorative care approaches within aged care with the aim of determining definitional clarity, key themes, and the professional groups delivering each approach. Methods Nine databases were searched (2012 to September 2023) to identify English-language systematic reviews on aged care-based rehabilitation, reablement and/or restorative care. Two reviewers independently screened studies following predetermined eligibility criteria. Only reviews reporting quality appraisal findings were eligible. Data charting and synthesis followed the Arksey and O’Malley approach and are reported according to PRISMA-ScR guidelines. Results Forty-one reviews met inclusion criteria. Most (68%) reported on rehabilitation in aged care, and eight (20%) combined the approaches. Only 14 reviews (34%) defined the approach they described. Reviews centred on services for older people in the home or community (n = 15), across a mix of settings including community, hospital, and residential care (n = 10). Ten distinct themes highlight the importance of multidisciplinary teams, allied health, risk of falls, hip fracture, reduced functional independence, and specific types of interventions including physical activity, technology, cognitive rehabilitation, goal setting, and transition care. Most reviews described the role of occupational therapists (n = 22), physiotherapists (n = 20) and nurses (n = 14) with wider support from the multidisciplinary team. The quality of primary studies within the reviews varied widely. Conclusions This scoping review summarises the evidence landscape for rehabilitation, reablement, and restorative care approaches in the context of aged care. Despite their role in enhancing independence and quality of life for older people, policy, funding, and terminology variation means the evidence lacks clarity. This fragmented evidence makes it challenging to argue the effectiveness of one approach over another for older people in receipt of aged care services. Clinical trial number Not applicable.